Meningkatkan Pembangunan Ekonomi Melalui Isomorfisme Institusional: Studi Kasus LazisMu Di Kota Depok - Fauziyah, Syifa; Jaharuddin, Jaharuddin; Ardiansyah, Ardiansyah; Syamsiah, Nurul (ITB AAS INDONESIA Surakarta, 2024)
This research aims to analyze the role and dynamics of the LazisMu institution in Depok City and examine its economic institutional design to improve performance through the lens of coercive, mimetic, and normative isomorphism theories. Utilizing a qualitative approach with interviews from seven informants, the findings indicate that LazisMu effectively reduces community uncertainty in the donation of zakat, infaq, and sadaqah, while enhancing social welfare, poverty alleviation, economic empowerment, and community participation. Coercive pressures promote financial transparency, mimetic pressures drive the adoption of best practices from successful organizations, and normative pressures underscore the necessity of human resources training. Future economic institutional designs should focus on the stringent application of coercive regulations, conducting comparative studies to stimulate change, and capacity building for staff. This study contributes to the literature on the economic role of LazisMu in the development of the Depok City community and provides insights into future economic institutional designs from an isomorphism perspective. The research outcomes are expected to positively impact LazisMu and other stakeholders, demonstrating that isomorphism theory can facilitate beneficial changes.